The magic faraway tree : a new adventure - Wilson, Jacqueline (London: Hodder Children's Books, 2022)
Three kids, Milo, Mia and Birdy, are on a countryside holiday when they wander into an Enchanted Wood. Among the whispering leaves, there is a beautiful tree that stands high above the rest. The Magic Faraway Tree is home to remarkable creatures including a fairy called Silky, her best friend Moonface and more. Birdy is delighted to find that fairies are real. Even her older brother and sister are soon won over by the magic of the Faraway Tree and the extraordinary places they discover above it, including the Land of Unicorns. But not every land is so much fun. Danger looms in the Land of Dragons. Will Moonface's magic work in time to save the children? The Magic Faraway Tree by Enid Blyton was Jacqueline Wilson's own favourite book as a young child. Now Britain's favourite contemporary children's author, creator of Hetty Feather and Tracy Beaker, revisits this glorious magical world, weaving a brand-new story perfect for the next generation of young readers. Discover the magic!
Keywords: Children's stories